A modest proposal on method : essaying the study of religion - McCutcheon, Russell T., 1961- (Supplements to Method & Theory in the Study of Religion, 2014)
A Modest Proposal on Method further documents methodological and institutional failings in the academic study of religion. This collection of essays-which includes three previously unpublished chapters-identifies the manner in which old problems (like the presumption that our object of study is a special, deeply meaningful case) yet remain in the field. But amidst the critique there are a variety of practical suggestions for how the science of religion can become methodologically even-handed and self-reflexive-the markings of a historically rigorous exercise. Each chapter is introduced and contextualized by a newly written, substantive introduction.